Effect of Plant-Derived n-3 Polyunsaturated Fatty Acids on Blood Lipids and Gut Microbiota: A Double-Blind Randomized Controlled Trial - Liu, Hongjie; Li, Xiaoqin; Zhu, Yalun; Huang, Yue; Zhang, Qin; Lin, Shan; Fang, Can; Li, Linyan; Lv, Yanling; Mei, Wenhua; Peng, Xiaolin; Yin, Jiawei; et al. (Frontiers in Nutrition, 2022)
Abstract Background: Several cardioprotective mechanisms attributed to n-3 polyunsaturated fatty acids (PUFAs) have been widely documented. Significant interest has recently focused on the role of human gut microbiota in metabolic disorders. However, the role of plant-derived n-3 PUFAs on blood lipid profiles is controversial and the effect on gut microbiota is still unclear. Objectives: We aimed to perform a double-blind randomized controlled trial to test the effect of plant-derived n-3 PUFAs on the blood lipids and gut microbiota of patients with marginal hyperlipidemia. Methods: According to the inclusion and exclusion criteria, 75 participants with marginal hyperlipidemia were randomly assigned to the intervention group (supplied with n-3 PUFA-enriched plant oil) or control group (supplied with corn oil), respectively, for a 3-month treatment. Participants and assessors were blinded to the allocation. The primary outcomes of the trial were the changes in serum lipid levels. Secondary outcomes were changes in gut microbiota and metabolites. For the primary outcomes, we conducted both an intent-to-treat (ITT) analysis and a per protocol (PP) analysis. For the secondary outcomes, we only conducted the PP analysis among the participants who provided fecal sample. Results: Fifty-one participants completed the trial. Relative to the control group, the n-3 PUFA supplementation resulted in significant reduction in total cholesterol (TC) levels (-0.43 mmol/L, 95% CI -0.84 to -0.01 mmol/L, P < 0.05). The n-3 PUFA supplementation was also associated with significantly increased relative abundance of Bacteroidetes in phylum level (P < 0.01; false discovery rate (FDR) corrected p = 0.11), and decreased the ratio between Firmicutes and Bacteroidetes (P < 0.05; FDR corrected p = 0.16). At genus level, the intervention of plant derived n-3 PUFAs resulted in a significant decrease in relative abundance of Phascolarctobacterium (P < 0.01; FDR corrected p = 0.18) and Veillonella (P < 0.01; FDR corrected p = 0.18) after the intervention. Conclusions: Our results demonstrated that plant-derived n-3 PUFAs beneficially affected the serum levels of TC and decreased the ratio between Firmicutes and Bacteroidetes during the 12-week intervention period, which might confer advantageous consequences for lipid metabolism and intestinal health. Trial registration number: HPG2017102074 (https://clinicaltrials.gov/).